PRESENCE OF C3 RECEPTORS ON DIFFERENT STRAINS OF PARACOCCIDIOIDES BRASILIENSIS - Carvalhaes, Mara Silvia (Revista de Patologia Tropical / Journal of Tropical Pathology, 2007)
Yeast fornis of Paracoccidioides braslliensis exprcss C3 receplors, as determined by r o sei t in gwith erylhrocytes carrying complemeni of C5 deficieni mice. Rosetling with EAC was markedly reducedon pathogenic strains (Pb.18 and Pb.SN), and appears preferentially on non pathogenic strain (1VICPb.267) or on a strain of relatively low virulence (IVIC Pb.9). Rosetling wilh EAC was not reduced whenyeast forms of ali strains were heat killed.